2013
DOI: 10.1016/j.pscychresns.2013.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Altered brain response to reward and punishment in adolescents with Anorexia nervosa

Abstract: Adults recovered from anorexia nervosa (AN) have altered reward modulation within striatal limbic regions associated with the emotional significance of stimuli, and executive regions concerned with planning and consequences. We hypothesized that adolescents with AN would show similar disturbed reward modulation within the striatum and the anterior cingulate cortex, a region connected to the striatum and involved in reward-guided action selection. Using functional magnetic resonance imaging, twenty-two adolesce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
85
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 40 publications
(72 reference statements)
5
85
1
Order By: Relevance
“…For example 224 adolescent AN patients exhibited an elevated neural response to punishment in the "cognitive" zone 225 of the dACC relative to HC in a monetary guessing task. (21). Conversely, Zastrow et al (24) found 226 decreased pMFC activation specifically on "shift" trials of a target detection task in AN.…”
Section: Imaging Data 187mentioning
confidence: 98%
See 2 more Smart Citations
“…For example 224 adolescent AN patients exhibited an elevated neural response to punishment in the "cognitive" zone 225 of the dACC relative to HC in a monetary guessing task. (21). Conversely, Zastrow et al (24) found 226 decreased pMFC activation specifically on "shift" trials of a target detection task in AN.…”
Section: Imaging Data 187mentioning
confidence: 98%
“…Suggesting that AN patients may be particularly 17 hypersensitive to punishment, patients have been also found to make less risky choices than healthy 18 controls (HC) in another decision-making paradigm, the Balloon Analogue Risk Task (13). Further 19 evidence comes from neuroimaging studies which found altered reward processing in response to 20 disorder-related stimuli like food or taste (16)(17)(18) and secondary reinforcers (19)(20)(21)(22)(23). For example, 21 neural response to punishment (monetary loss) has been found to be elevated in acutely ill 22 adolescents in corticostriatal regions involved in valuation and action selection (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the clinical presentation, several functional neuroimaging studies have focused on the processing of food/taste and other appe titive stimuli. [4][5][6][7][8][9] Results suggest that patients may have an al tered sensitivity for sensory interoceptive and/or reward processes as well as an impaired awareness of homeostatic needs. 10 However, published reports revealed considerable inconsistencies, which may be explained by substantial vari ability among studies, including issues with task design, stimulus selection and varying cognitive abilities of the starv ing participants.…”
Section: Introductionmentioning
confidence: 99%
“…Based on self-report or behavioural data, some researchers have suggested reduced reward sensitivity in patients with anorexia nervosa, 42,43 but others have reported no group differences. 44 While an fMRI study in recovered patients 10 using a guessing game pointed to a general dysfunction of the reward system in patients with anorexia nervosa, this finding could not be verified in acutely underweight adolescents with anorexia nervosa, 45 suggesting that the abnormalities may not represent a trait effect. Using disease-relevant stimuli, such as food or thin body images, other studies have reported a hyposensitivity 17 or hypersensitivity of the brain reward system in recovered adults 12,43 and in adults 13 and adolescents 46 with acute anorexia nervosa.…”
mentioning
confidence: 98%